Open Source IoT-Based SCADA System for Remote Oil Facilities Using Node-RED and Arduino Microcontrollers - Osaretin, Charles Aimiuwu; Zamanlou, Mohammad; Iqbal, M. Tariq; Butt, Stephen (IEEE Annual Information Technology, Electronics and Mobile Communication Conference (Online), 2020)
An open source and low-cost Supervisory Control and Data Acquisition System based on Node-RED and Arduino microcontrollers is presented in this paper. The system is designed for monitoring, supervision, and remotely controlling motors and sensors deployed for oil and gas facilities. The Internet of Things (IoT) based SCADA system consists of a host computer on which a server is deployed using the Node-RED programming tool and two terminal units connected to it: Arduino Uno and Arduino Mega. The Arduino Uno collects and communicates the data acquired from the temperature, flowrate, and water level sensors to the Node-Red on the computer through the serial port. It also uses a local liquid crystal display (LCD) to display the temperature. Node-RED on the computer retrieves the data from the voltage, current, rotary, accelerometer, and distance sensors through the Arduino Mega. Also, a web-based graphical user interface (GUI) is created using Node-RED and hosted on the local server for parsing the collected data. Finally, an HTTP basic access authentication is implemented using Nginx to control the clients' access from the Internet to the local server and to enhance its security and reliability.